2015
DOI: 10.7759/cureus.369
|View full text |Cite
|
Sign up to set email alerts
|

Retrosigmoid Versus Translabyrinthine Approach for Acoustic Neuroma Resection: An Assessment of Complications and Payments in a Longitudinal Administrative Database

Abstract: ObjectRetrosigmoid (RS) and translabyrinthine (TL) surgery remain essential treatment approaches for symptomatic or enlarging acoustic neuromas (ANs). We compared nationwide complication rates and payments, independent of tumor characteristics, for these two strategies.MethodsWe identified 346 and 130 patients who underwent RS and TL approaches, respectively, for AN resection in the 2010-2012 MarketScan database, which characterizes primarily privately-insured patients from multiple institutions nationwide.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Nationwide databases are increasingly employed for analyses of trends across the population and may provide a valuable resource for uncommon pathologies such as skull base tumors. [2][3][4][5][6][7][8] Aggregated data mitigate certain biases inherent to single institution data and small sample sizes and has been applied to study risk factors for negative clinical outcomes, readmissions, and re-operations for surgical procedures. Additionally, the availability of CPT codes in large de-identified databases has prompted conclusions regarding specific surgical approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nationwide databases are increasingly employed for analyses of trends across the population and may provide a valuable resource for uncommon pathologies such as skull base tumors. [2][3][4][5][6][7][8] Aggregated data mitigate certain biases inherent to single institution data and small sample sizes and has been applied to study risk factors for negative clinical outcomes, readmissions, and re-operations for surgical procedures. Additionally, the availability of CPT codes in large de-identified databases has prompted conclusions regarding specific surgical approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Databases that include CPT coding are especially relevant for relatively uncommon pathologies such as vestibular schwannoma. [2][3][4][5][6][7][8] Despite these advantages, increased attention has been directed toward the limitations and potential inaccuracies of national databases for neurosurgical research. 9,10 While the inter-rater reliability of databases has been rated as good, there remains limited knowledge on whether databases precisely reflect the nuances of coding for skull base pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…The approach utilized is based on the patient's hearing, tumor location and size, and surgeon's preference. 2 In general, the RS approach is considered more versatile and is used in patients with serviceable hearing. 3 The TL approach is used in patients with nonserviceable hearing or in patients with large tumors who have a low probability of hearing preservation.…”
Section: Introductionmentioning
confidence: 99%
“…3 One United States-based review concluded that TL surgery had lower risks of postoperative facial nerve injury, dysphagia, and dysrhythmia, but no difference in 30-day general complications or cerebrospinal fluid (CSF) leak repair rates. 4 They however did not measure LOS. A separate US cost effectiveness analysis found a lower hospital (but not intensive therapy unit [ITU]) LOS in TL versus RS approach.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients who have a longer stay in hospital may be at risk of hospital-related complications, such as infection and thrombosis. As tumor size is a known factor for prognosis affecting neurological outcome and complication rate, 4 we hypothesized that tumor size is a key variable determining LOS and factored this into our research question.…”
Section: Introductionmentioning
confidence: 99%